Search for heavy neutrinos or third-generation leptoquarks in final states with two hadronically decaying tau leptons and two jets in proton-proton collisions at root s=13 TeV - Khachatryan, V. (2017)
A search for new particles has been conducted using events with two high transverse momentum ((pT)) T leptons that decay hadronically, at least two high-pT jets, and missing transverse energy from the T lepton decays. The analysis is performed using data from proton-proton collisions, collected by the CMS experiment in 2015 at root s = 13 TeV, corresponding to an integrated luminosity of 2.1 fb(-1). The results are interpreted in two physics models. The first model involves heavy right-handed neutrinos, N-l (l = e, mu, T), and right-handed charged bosons, WR, arising in a left-right symmetric extension of the standard model. Masses of the W-R boson below 2.35 (1.63) TeV are excluded at 95% confidence level, assuming the N-tau mass is 0.8 (0.2) times the mass of the W-R boson and that only the NT flavor contributes to the WR decay width. In the second model, pair production of third-generation scalar leptoquarks that decay into (TT)bb is considered. Third-generation scalar leptoquarks with masses below 740 GeV are excluded, assuming a 100% branching fraction for the leptoquark decay to a T lepton and a bottom quark. This is the first search at hadron colliders for the third-generation Majorana neutrino, as well as the first search for third-generation leptoquarks in the final state with a pair of hadronically decaying T leptons and jets.